2016
DOI: 10.22201/iie.18703062e.2016.109.2579
|View full text |Cite
|
Sign up to set email alerts
|

Los diseños en la cestería seri: ensayo sobre técnicas de vinculación social

Abstract: El objeto de este artículo es describir, desde la organización del co-nocimiento y de la práctica de algunas tejedoras seris de El Desemboque, Sonora, qué significan los diseños en la cestería. Mostraré que éstos son a) índices de las relaciones que se establecen durante su elaboración y transmisión (la variación individual, la construcción del consenso familiar y de la “tradición”) y b) técnicas de vinculación para producir, reproducir e intensificar su sociedad. Asimismo, exploro el problema de la variabilid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In South America, there are references to the indigenous society of the Venezuelan Amazon, where basketry acts as a mediator with the westernized world [33]. In Mexico, the meanings of the basketry designs are analyzed, and it can be shown that the flexibility tests on wood have no scientific basis [34]. In Ecuador, the collection, management, use, and commercialization of plants are addressed, with special emphasis on basketry.…”
Section: Documentary Analysis Qualitative and Quantitative Aspectsmentioning
confidence: 99%
“…In South America, there are references to the indigenous society of the Venezuelan Amazon, where basketry acts as a mediator with the westernized world [33]. In Mexico, the meanings of the basketry designs are analyzed, and it can be shown that the flexibility tests on wood have no scientific basis [34]. In Ecuador, the collection, management, use, and commercialization of plants are addressed, with special emphasis on basketry.…”
Section: Documentary Analysis Qualitative and Quantitative Aspectsmentioning
confidence: 99%